The Cartoonists Club - Telgemeier, Raina; McCloud, Scott, 1960-; Baehr, Ray; Hollman, Beniam C.; Post, Jesse (New York, NY : Graphix, an imprint of Scholastic, 2025)
"Makayla is bursting with ideas but doesn't know how to make them into a story. Howard loves to draw, but he struggles to come up with ideas and his dad thinks comics are a waste of time. Lynda constantly draws in her sketchbook but keeps focusing on what she feels are mistakes, and Art simply loves being creative and is excited to try something new. They come together to form The Cartoonists Club, where kids can learn about making comics and use their creativity and imagination for their own storytelling adventures!"--Provided by publisher.
Includes bibliographical references.
Keywords: Cartoonists -- Comic books, strips, etc; Clubs -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Cartoonists -- Fiction; Clubs -- Fiction; Friendship -- Fiction; Cartoons and comics; Graphic novels; Comics (Graphic works)